2016
DOI: 10.3389/fendo.2015.00192
|View full text |Cite
|
Sign up to set email alerts
|

Proteome-Wide Effect of 17-β-Estradiol and Lipoxin A4 in an Endometriotic Epithelial Cell Line

Abstract: Endometriosis affects approximately 10% of women of reproductive age. This chronic, gynecological inflammatory disease results in a decreased quality of life for patients, with the main symptoms including chronic pelvic pain and infertility. The steroid hormone 17-β Estradiol (E2) plays a key role in the pathology. Our previous studies showed that the anti-inflammatory lipid Lipoxin A4 (LXA4) acts as an estrogen receptor-alpha agonist in endometrial epithelial cells, inhibiting certain E2-mediated effects. LXA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…In these studies, patients were at least 3–6 months without hormonal or anti-inflammatory treatment. ESCs were treated in cell culture with the mediator under investigation, and the evaluation was carried out through several types of laboratory analysis [ 7 , 19 , 30 , 31 , 33 , 34 , 35 ]. Rasheed et al analyzed in vitro halogenic stem cells by adding serum from patients diagnosed with endometriosis to evaluate cell differentiation and the expression of ANXA1 [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In these studies, patients were at least 3–6 months without hormonal or anti-inflammatory treatment. ESCs were treated in cell culture with the mediator under investigation, and the evaluation was carried out through several types of laboratory analysis [ 7 , 19 , 30 , 31 , 33 , 34 , 35 ]. Rasheed et al analyzed in vitro halogenic stem cells by adding serum from patients diagnosed with endometriosis to evaluate cell differentiation and the expression of ANXA1 [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…LXA4 reduced pro-inflammatory cytokines in lesions, ESCs and peritoneal fluid cells during in vivo and in vitro experiments. Among the studied cytokines, treatment with LXA4 reduced the expression of interleukine 1β (IL-1β), interleukin 6 (IL-6), interleukin 10 (IL-10), interleukin 16 (IL-16), vascular endothelial growth factor (VEGF), TNF, transforming growth factor (TGF)-β1 and TGF-β2 [ 19 , 27 , 29 , 31 , 32 , 33 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To identify endometriosis biomarkers, several sample types including serum, peritoneal fluid, endometriotic lesion and endometriotic epithelial cell have been used. 19,[28][29][30][31] In this study, we first obtained primary ESC, and then used them as an in vitro model to identify altered proteins after treatment with IL-1β or LXA 4 . To our knowledge, endometriosis is also an inflammatory disease.…”
Section: Discussionmentioning
confidence: 99%
“…12,15 Data from our research group and others have shown that LXA 4 elicits anti-inflammatory, anti-angiogenic and antiproliferative actions in endometriotic stromal cells (ESC) and glandular epithelial cells, by reducing the expression of inflammatory factors and estrogen signaling. [16][17][18][19] Although the roles of IL-1β and LXA 4 have been intensively studied, little is known about the effect of LXA 4 on IL-1β in endometriosis. To understand the modulation mechanisms of LXA 4 in preventing the development and progression of endometriosis by influencing the effect of IL-1β, a study of the proteome in response to treatment with IL-1β or LXA 4 is essential.…”
Section: Introductionmentioning
confidence: 99%